The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.14306/renhyd.21.1.220
|View full text |Cite
|
Sign up to set email alerts
|

Efectos de los suplementos de proteína y aminoácidos de cadena ramificada en entrenamiento de fuerza: revisión bibliográfica

Abstract: Introducción: Los suplementos de proteína y aminoácidos de cadena ramificada (BCAAs) son consumidos por la población buscando una serie de efectos fisiológicos y metabólicos sobre el rendimiento y recuperación, entre otros. Objetivo: Revisar las publicaciones más recientes que estudien los efectos del consumo de suplementos de proteína y BCAAs en entrenamiento de fuerza en diferentes parámetros fisiológicos y metabólicos. Material y Métodos:Estudio descriptivo de revisión bibliográfica. Se realizó una búsqueda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 66 publications
0
4
0
3
Order By: Relevance
“…Supporting the aforementioned, Rabassa-Blanco et al published a review on the effect of protein and BCAA supplements on changes in body composition, muscle mass, central or peripheral fatigue, muscle strength, muscle damage, and anabolic response in muscle recovery. They showed that protein supplements, in association with a balanced diet and training, can improve performance and muscle mass [ 19 ]. Despite the number of studies on BCAAs, there seems to be no consensus on the recommended amount per dose in relation to training.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Supporting the aforementioned, Rabassa-Blanco et al published a review on the effect of protein and BCAA supplements on changes in body composition, muscle mass, central or peripheral fatigue, muscle strength, muscle damage, and anabolic response in muscle recovery. They showed that protein supplements, in association with a balanced diet and training, can improve performance and muscle mass [ 19 ]. Despite the number of studies on BCAAs, there seems to be no consensus on the recommended amount per dose in relation to training.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the number of studies on BCAAs, there seems to be no consensus on the recommended amount per dose in relation to training. Of all the BCAAs, specifically, leucine has shown positive effects on muscle mass, in reducing central fatigue and consequently improving performance [ 19 , 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin is an anticatabolic, which achieves muscle protein anabolism by the inhibition of muscle protein breakdown [22], so CHO intake after exercise could be beneficial to potentiate exercise-induced adaptations. However, evidence is mixed in this regard, and it seems that supplying an optimal amount of high-quality proteins, specifically proteins that contain an adequate dose of leucine (e.g., 3–4 g/dose) [23] after exercise can be enough to achieve a positive protein balance and stimulate an anabolic response [24]…”
Section: Carbohydrates and Training Adaptationsmentioning
confidence: 99%
“…Las proteínas son un componente vital para el organismo siendo esenciales para el crecimiento y el mantenimiento de las estructuras corporales. También pueden ser utilizadas como fuente de energía en ausencia de los carbohidratos y grasas, sin embargo, no es una función que deban cumplir (Rabassa & Palma, 2017).…”
Section: Introductionunclassified